Emerging advances in synthetic cancer nano-vaccines: opportunities and challenges. (1st November 2020) - Ahmad, Mohammad Zaki; Ahmad, Javed; Haque, Anzarul; Alasmary, Mohammed Yahia; Abdel-Wahab, Basel A.; Akhter, Sohail
ABSTRACT: Introduction : Cancer immunotherapy is a fast-growing field that has achieved tremendous progress in recent years. It is one of the most potent tools that can activate the immune system against cancer. Nevertheless, the development of safe and effective vaccines to overcome emerging new disease remains challenging since several emerging antigens are poorly immunogenic. Nanotechnology has provided a realistic resolution for the drawback of traditional cancer immunotherapy. Area covered : This review discusses different cancer immunotherapy approaches focusing on recent advancements in nanomedicine-based cancer immunotherapy. The literature review method includes inclusion and exclusion criteria to categorize important articles. The literature survey was carried out using PubMed, Google Scholar, Scopus, and the Saudi digital library. Expert opinion : In the last two decades, the development and application of nanoparticles incorporating antigen/adjuvant in cancer immunotherapy have experienced rapid growth. Soon, progressively multifaceted nanovaccines presenting different antigens and co-delivered with antigens will be clinically translated. Better understanding and improved knowledge of nanomedicines-based delivery approaches and immunostimulatory action, and in-vivo biodistribution would inevitably facilitate the altruistic design of cancer nanovaccine for humankind.